Housing and Summer Management Practices Followed by Buffalo Farmers in Yanam Region of Puducherry - K. Prasanthi; R. Mallikarjuna; D. Sreekumar; V. Rajaganapathy; R. Ganesan; K. Natchimuthu (The Indian Veterinary Journal, 2025)
A study was carried out to find out the housing management practices of buffaloes in Yanam region, Union Territory (UT) of Puducherry. A total of 150 respondents were selected at random for the study. The study revealed that 88.0 per cent of the farmers housed their buffaloes in kutcha type sheds with thatched roof (74.8%) and mud flooring (89.4%). Manger was provided by (85.3%) of the respondents. Majority of the buffalo farmers were heaping dung on the land and later used as farm yard manure. Proper ventilation facility was observed in the buffalo sheds. The study suggested that improving knowledge on housing management among the buffalo farmers of Yanam region would result in better buffalo management leading to better livelihood.